Kedudukan Dan Peran Organisasi Profesi Advokat Terhadap Advokat Yang Berhadapan Dengan Hukum - Endira, Bramedika Kris; Junaidi, Muhammad; Ratna Sediati, Diah Sulistyani; Sihotang, Amri Panahatan (Universitas Semarang, 2022)
This study aims to determine the role of an advocate organization, in this case: The Indonesian Advocates Association (Peradi) in maintaining the dignity of its advocates who are addressing the law. Sociologically, the advocate profession is a free and independent profession and is responsible for law enforcement. However, juridically, because advocates are